2003
DOI: 10.5713/ajas.2003.1770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Glutamine Supplement on Performance and Intestinal Morphology of Weaned Pigs

Abstract: Two experiments were conducted to investigate the effect of dietary glutamine (Gln) supplement on the performance and villus morphology of weaned pigs. In Exp. 1, 48 pigs were fed diets supplemented with 0, 0.5, 1.0, or 1.5% Gln for 28 days. Dietary Gln supplemented levels did not influence performance and plasma Gln concentration of weaned pigs. In Exp. 2, 48 weaned pigs were fed the same treatment diets of Exp. 1 for 7 or 14 days. Dietary Gln supplement reduced the ratio of small intestine weight to empty ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
4
17
0
2
Order By: Relevance
“…In the present study, there was no significant effect of 1% dietary glutamine in improving growth performance of the weaned pigs. This result is consistent with that of Lee et al (2003). However, Wu et al (1996) found that the dietary supplementation of glutamine (1%) improved the gain:feed ratio of weaned pigs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, there was no significant effect of 1% dietary glutamine in improving growth performance of the weaned pigs. This result is consistent with that of Lee et al (2003). However, Wu et al (1996) found that the dietary supplementation of glutamine (1%) improved the gain:feed ratio of weaned pigs.…”
Section: Discussionsupporting
confidence: 92%
“…Glutamine is known to be an abundant amino acid in both physiological fluids and proteins and a key regulator of gene expression (Wu et al, 2011). Dietary Gln had no effect on the concentration of Gln in the plasma on day 14 of postweaning piglets (Lee et al, 2003;Zhou et al, 2006). Yoo et al (1997) reported that the concentration of Gln in the plasma was not affected by the addition of 4% Gln in diets of pigs weaned at 21 days of age.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Glutamine (Wu et al, 1995) and glutamate (Reeds et al, 2000) are important fuels for intestinal epithelial cells. Notwithstanding the stresses of weaning, these AA were able to maintain the high turnover of the gut mucosa, as indicated by longer villi in pigs supplemented with glutamine (Ayonrinde et al, 1995;Liu et al, 2002;Lee et al, 2003;Domeneghini et al, 2004 and or glutamate (Liu et al, 2002). For glutamine, this was determined by a decrease in the apoptotic to mitotic mucosal cell ratio (Domeneghini et al, 2004 and.…”
Section: Specific Amino Acidsmentioning
confidence: 99%
“…Wu, Meier y Knabe, 1996;Lee y col., 2003;Domeneghini y col., 2004;Zhou y col., 2006;Zou y col., 2006;Abreu y col., 2010;Hsu y col., 2010;Shan y col., 2012;Xiao y col., 2012;Wang y col., 2014;He y col., 2016;Duttlinger y col.…”
unclassified